Sanksi Pidana Untuk Korporasi dan Pemegang Saham Korporasi Atas Tindak Pidana Lingkungan Hidup - Suryani Alawiyah; Irwan Triadi (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The seriousness of the Indonesian government in paying attention to the environment is manifested in the existence of Law Number 32 of 2009 concerning Environmental Management by regulating criminal liability for corporate legal subjects subject to criminal penalties. This is because many environmental crimes are committed by corporations and may also be carried out by corporate shareholders as policy controllers of a corporation. Against the background of environmental criminal acts which are often committed by corporations and even shareholders are also involved in these criminal acts, this article aims to provide an illustration that shareholders can also be given criminal sanctions. The method used in this research is normative juridical with a literature study approach. The results of this research explain that corporations that commit environmental crimes are clearly regulated in Law Number 32 of 2009 so that criminal sanctions can be given to provide deterrence to corporate perpetrators, but for corporate shareholders involved it is not yet explicitly regulated in Law Number 32 of 2009. 2009 because they have not adopted the Piercing the corporate veil doctrine and the alter ego doctrine as in Law Number 40 of 2007 concerning Limited Liability Companies in article 3 paragraph (2) which eliminates the immunity rights of shareholders so that they can be punished.